2016
DOI: 10.14393/bj-v32n5a2016-33001
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory activity in wheat seeds as related to physiological quality

Abstract: Seeds are a very important input for crops, and the use of low quality seeds and/or inadequate management affects the germination and hampers seedling emergence, which reduces the plant stand. There is a critical need for the development of rapid methods, which are both reliable and easy to perform, for evaluating the physiological potential of seeds. This would streamline the decision-making process regarding the management of lots and allow for the identification of seed lots of inadequate quality in the see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…By the respiratory activity measured by Pettenkofer physicochemical method (Table 4), in which is evaluated the amount of CO 2 released by the respiration of the seeds per gram of seed per hour, it was possible to statistically separate all the seed lots in six levels of vigor. Similar behavior was found by Torres et al (2016) and Dode et al (2016) that, working with E. sativa and T. sativum, respectively, verified the efficiency of the Pettenkofer method in statistically separating lots at quality levels.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…By the respiratory activity measured by Pettenkofer physicochemical method (Table 4), in which is evaluated the amount of CO 2 released by the respiration of the seeds per gram of seed per hour, it was possible to statistically separate all the seed lots in six levels of vigor. Similar behavior was found by Torres et al (2016) and Dode et al (2016) that, working with E. sativa and T. sativum, respectively, verified the efficiency of the Pettenkofer method in statistically separating lots at quality levels.…”
Section: Resultssupporting
confidence: 81%
“…Similar studies were conducted with Zea mays L. , Eruca sativa L. (Torres et al, 2016), Triticum sativum L. (Dode et al, 2016), Citrullus lanatus [Thunb.] Matsum and Nakai (Oliveira et al, 2015) among others, proving the efficiency of the methods in differentiating lots with different vigor levels.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the present research, the respiratory activity of seeds from different seed lots was higher the lower the physiological quality, in accordance with Dode et al (2013) with seeds of Glicine max L., Martins et al (2014) with seeds of Z. mays and Dode et al (2016) with seeds of Triticum aestivum L., which observed an inverse relationship between CO 2 concentration released by seeds and their physiological quality.…”
Section: Number Of Seeds Seed Lotsupporting
confidence: 89%
“…However, for genotype "B", considering absolute values, large flat seeds originated seedlings with higher total dry mass, however, they were statistically similar to those from large round seeds, while the total dry mass of seedlings originated from small flat seeds and small round were inferior, not differing between themselves, indicating less vigor. Dode et al (2016), evaluating the efficiency of Pettenkofer´s method to determine respiratory activity of wheat seed lots with different vigor levels, observed that seedlings with the highest total mass were those originated from seeds with higher vigor. In this sense, it should be emphasized that larger seeds tend to originate larger seedlings compared to those from smaller seeds (Stumm et al, 2016).…”
Section: Genmentioning
confidence: 99%